Aerobic biological pretreatment of municipal solid waste with a high content of putrescibles: effect on landfill emissions. Issue 8 (August 2013) - Gerassimidou, Spyridoula; Evangelou, Alexandros; Komilis, Dimitrios
The objective of this work was to study the effect of aerobic biological pretreatment on the emissions of municipal solid waste (MSW) with a high content of putrescibles after landfilling. For this purpose, the organic fraction of MSW was simulated by a mixture of food waste and office paper at a 2.4:1 wet weight ratio. MSW was first pretreated aerobically for three different time periods (8, 45 and 90 days) resulting in organic matter reductions equal to 15%, 45% and 81% respectively. MSW were then placed in 160-L air-tight anaerobic bioreactors. The control anaerobic bioreactors contained untreated MSW. Anaerobic experiments lasted from 300 to 550 days. Results showed that the biogas production from untreated MSW was 372 NL dry kg -1 (average of two replications) after 530 days. The MSW that was pretreated aerobically for 45 days and 90 days yielded 130 and 62 NL dry kg -1 of biogas after 310 days and 230 days respectively. However, the 8-day (very short-term) pretreatment period led to an increase of the biogas yield (550 NL dry kg -1 after 340 days) compared with that of raw refuse. All three runs with aerobically pretreated MSW reached the steady methanogenic phase faster than raw MSW. Leachate emissions were significantly lower in the aerobically-pretreated MSWthan the untreated ones. The leachate ammonium concentrations had an increasing trend in all anaerobic reactors and reached a plateau of between 2 and 3.5 g L -1 at the end of the process.